Properties for component model: the definition perspective - Aris, H.; Salim, S.S. (2011)
The presence of a large number of component models to date should be able to offer software developers a wide variety of component models - which they can easily choose from - for their software development projects. However, the opposite situation is currently observed, where the presence of many component models has caused difficulties in making the selection. Lack of properties or characteristics that can be used as a basis to perform objective comparison between the existing models is believed to have caused the difficulties. In this paper, a list of component model properties is derived by thoroughly examining the available component model definitions. Results from a comparative analysis performed on six component models using the properties show that the properties enable a more objective comparison between the existing component models to be performed.